Band alignment in organic light emitting diodes - On the track of thickness dependent onset voltage shifts - Kühn, Maybritt; Glaser, Tobias (Organic electronics, 2017)
In this paper we report on an unclear effect in the IV characteristics of organic light emitting diodes (OLEDs). When the thickness of the emitter layer based on a modified phenyl carbozole triplet host material (TH) in the device is increased, a significant shift of the onset voltage to higher values can be noticed. The voltage shift is not observed if the TH is substituted by an isomer with only minor variation of the molecular structure. In a previous publication we could already show that an electric interface field is necessary to describe the onset voltage behaviour. To find the origin of this interface field in the present publication the two isomers are characterized and the band alignment at the interfaces to the emitter layer is investigated using photoelectron spectroscopy. The interface energy diagrams have been measured on stepwise prepared model interfaces. A further simplification of the bipolar to a hole only device stack proofs, that band bending at the hole injecting interface to the TH layer is the origin of the interface field. In contrast an entire flat band situation is measured in case of the device using the other isomer showing no onset voltage shift.
Available online 8 December 2016
Gesehen am 27.11.2018